The changing piety and spirituality: a new trend of Islamic urbanism in Yogyakarta and Surakarta - Alam, Lukis; Setiawan, Benni; Harimurti, Shubhi Mahmashony; Miftahulhaq, Miftahulhaq; Alam, Meredian (IAIN Salatiga, 2023)
The prevalence of urban spiritualism is on the rise among residents of major cities.One observable manifestation of urban spiritualism is the growing number ofdiverse social recitation gatherings. The present research looks into four distinctprofiles of assemblies that have emerged in the urban areas of Yogyakarta andSurakarta. The four assemblies comprise Muslim United and Teras Dakwah. InSurakarta, it is worth noting the presence of two prominent organisations, namelyMajelis Ar-Raudhah, established by Habib Novel Alaydrus, and Majelis BusytanulAsyiqin, founded by Habib Syech Assegaf. This study elucidates the techniquesemployed by the aforementioned four assemblies to disseminate moderatereligious knowledge within urban circles, as well as their respective reactions tothe evolving spiritual dynamics observed within urban communities. The presentstudy employs a qualitative methodology, specifically a field study approach. Thefindings of this study suggest a shift in the dominance of religious authority amongrenowned ustadz and habaib figures. By endorsing the dissemination of widelyrecognised da’wah conducted by these prominent individuals, it contributesto the enhancement of religious literacy among urban populations. The studyfindings also interpret the santrinisation and piety activities observed in urbancommunities as a tangible expression of the veracity of religious teachings.